Analysis of COVID-19 CT Chest Image Classification using Dl4jMlp Classifier and Multilayer Perceptron in WEKA Environment - S., Sreejith; Ajayan, J.; Reddy, N.V.Uma; S., Babu Devasenapati; Rebelli, Shashank (Current Medical Imaging, 2024)
IntroductionIn recent years, various deep learning algorithms have exhibited remarkable performance in various data-rich applications, like health care, medical imaging, as well as in computer vision. COVID-19, which is a rapidly spreading virus, has affected people of all ages both socially and economically. Early detection of this virus is therefore important in order to prevent its further spread.MethodsCOVID-19 crisis has also galvanized researchers to adopt various machine learning as well as deep learning techniques in order to combat the pandemic. Lung images can be used in the diagnosis of COVID-19.ResultsIn this paper, we have analysed the COVID-19 chest CT image classification efficiency using multilayer perceptron with different imaging filters, like edge histogram filter, colour histogram equalization filter, color-layout filter, and Garbo filter in the WEKA environment.ConclusionThe performance of CT image classification has also been compared comprehensively with the deep learning classifier Dl4jMlp. It was observed that the multilayer perceptron with edge histogram filter outperformed other classifiers compared in this paper with 89.6% of correctly classified instances.
Keywords: WEKA